Design and Fabrication of an Active Knee Orthosis for Rehabilitation of Lower Limbs - Mohammad Amin Iravani Rad; Ali Mokhtarian; Mohammad Taghi Karimi (Shiraz University of Medical Sciences, 2019)
Background: The main objective of this study is to design and produce a twolink active knee orthosis with 2 degrees of freedom to rehabilitate patients' lower extremities in moving their feet. This study aimed to provide motor independence in patients with cerebrospinal cord injury, quadriceps and knee joint injuries in athletes, and deviation of the quadriceps angle in the elderly. Methods: The current research is an experimental method. We have tried, while eliminating a physiotherapist, to enable movement modification of organs that suffer from dynamics poverty and ensure an improved movement for injured organs. In order to reduce external fluctuations and turbulences and determine orthosis opening and closing angle, a DC motor with a helical gearbox and a PID controller was used. In addition, an Arduino microcontroller and a potentiometer were used for processing and angle determination, respectively, to provide minimum wiring and maximum accuracy and performance for the proposed orthosis. Results: In order to verify the mechanical parts of the proposed orthosis, three tests were performed with different angles without charging the orthosis. Conclusion: Results showed that the proposed orthosis admissibly tracked intended angles and had a proper weight and volume to provide safety and comfort for the foot and knee joint.